3D-printable thermoactive helical interface with decentralized morphological stiffness control for continuum manipulators - Sadati,SH; Sullivan,L; Walker,ID; Althoefer,K; Nanayakkara,DPT (Institute of Electrical and Electronics Engineers, 2018)
We present a three-dimensional (3-D)-printable thermoactive scale jamming interface as a new way to control a continuum manipulator dexterity by taking inspiration from the helical arrangement of fish scales. A highly articulated helical interface is 3-D-printed with thermoactive functionally graded joints using a conventional 3-D printing device that utilizes UV curable acrylic plastic and hydroxylated wax as the primary and supporting material. The joint compliance is controlled by regulating wax temperature in phase transition. Empirical feed-forward control relations are identified through comprehensive study of the wax melting profile and actuation scenarios for different shaft designs to achieve desirable repeatability and response time. A decentralized control approach is employed by relating the mathematical terms of the Cosserat beam method to their morphological counterparts in which the manipulator local anisotropic stiffness is controlled based on the local stress and strain information. As a result, a minimalistic central controller is designed in which the joints' thermomechanical states are observed using a morphological observer, an external fully monitored replica of the observed system with the same inputs. Preliminary results for passive shape adaptation, geometrical disturbance rejection, and task space anisotropic stiffness control are reported by integrating the interface on a continuum manipulator.